“Students’ perceptions about the use of lyrics training to enhance listening comprehension” - Quiña Calispa, Katherine Lizbeth (2022)
Lyrics Training is a technological tool used in the educational field that will provide benefits in the motivation of the learning process and in the improvement of the student's skills, especially listening comprehension, which is a fundamental skill in the acquisition of a foreign language. This qualitative study aims to analyze the students’ perception of the use of Lyrics Training to enhance listening comprehension. Data was collected by means of a survey with eight questions and analyzed through the thematic analysis process. Participants were eighteen students from the eighth semester of English at the Technical University of Cotopaxi during April - August 2022 academic term. The main findings show the positive influence based on the participants' opinions through the use of Lyrics Training which enabled them to develop their listening comprehension. As for the benefits, they highlighted the accessibility of the website, which helped to improve spelling and pronunciation, as well as the enjoyment of learning, which allowed them to feel motivated and increase their vocabulary knowledge. On the other hand, they also faced some difficulties due to their lack of understanding of the colloquial words in the songs and technological problems that impeded the listening process. Finally, the application of Lyrics Training is considered a useful technological tool to learn and develop skills in a foreign language such as English. Based on these findings, it is suggested that teachers can adapt Lyrics Training in their classroom lessons to develop listening comprehension activities that will help them to achieve satisfactory performance in their students.